ANALISIS FAKTOR YANG MEMPENGARUHI â€œPREHOSPITAL DELAY TIMEâ€ PADA PASIEN NON-ST ELEVATION MYOCARDIAL INFARCTION (NSTEMI) - Widyarani, Linda (Jurnal Media Ilmu Kesehatan, 2018)
Background: AMI is the leading cause of morbidity and disability among Indonesian population. In referrals centre hospital, in-hospital mortality of NSTEMI is equal or even exceeds STEMI, increased from 17% to 21% during 12 months. Prehospital delay is an important cause of increasing early and also late mortality in NSTEMI. Objective: We investigated factors associated with prolonged prehospital delay in patients with NSTEMI. Method: In this cross-sectional study design, data were analyzed by chi-square and one-way ANOVA using SPSS 20 and data were collected from 50 patients with NSTEMI using patient?s medical notes and semi- structured interviews. Patients were pain-free and hemodynamically stable at the time of interview. Data were collected on the time from the onset of chest pain to hospital admission. Results: Mean of prehospital delay times were 7,89±1,44 hours. The predictor were singularly significantly associated with prolonged prehospital delay were self medication and health care seeking pattern. Traditional healers had longest prehospital delay time (24,30±2,65hours). Most of the people in Java from various social strata still believe in traditional healers (dukun) to treat their disease. Conclusion: Health care providers can educate the public on NSTEMI to enable them recognize the signs and symptoms of NSTEMI correctly and realize the benefits of early treatment. Keyword: Prehospital delay time and NSTEMI